Regenerative Intestinal Stem Cells Induced by Acute and Chronic Injury: The Saving Grace of the Epithelium? - Rees, William D.; Tandun, Rene; Yau, Enoch; Zachos, Nicholas C.; Steiner, Theodore S. (Frontiers in Cell and Developmental Biology, 2020)
The intestinal epithelium is replenished every 3-4 days through an orderly process that maintains important secretory and absorptive functions while preserving a continuous mucosal barrier. Intestinal epithelial cells (IECs) derive from a stable population of intestinal stem cells (ISCs) that reside in the basal crypts. When intestinal injury reaches the crypts and damages IECs, a mechanism to replace them is needed. Recent research has highlighted the existence of distinct populations of acute and chronic damage-associated ISCs and their roles in maintaining homeostasis in several intestinal perturbation models. What remains unknown is how the damage-associated regenerative ISC population functions in the setting of chronic inflammation, as opposed to acute injury. What long-term consequences result from persistent inflammation and other cellular insults to the ISC niche? What particular “regenerative” cell types provide the most efficacious restorative properties? Which differentiated IECs maintain the ability to de-differentiate and restore the ISC niche? This review will cover the latest research on damage-associated regenerative ISCs and epigenetic factors that determine ISC fate, as well as provide opinions on future studies that need to be undertaken to understand the repercussions of the emergence of these cells, their contribution to relapses in inflammatory bowel disease, and their potential use in therapeutics for chronic intestinal diseases.